Dielectric properties of dog brain tissue measured in vitro across the 0.3–3 GHz band. Issue 8 (22nd September 2016) - Mohammed, Beadaa; Bialkowski, Konstanty; Abbosh, Amin; Mills, Paul C.; Bradley, Andrew P.
Abstract : Dielectric properties of dead Greyhound female dogs' brain tissues at different ages were measured at room temperature across the frequency range of 0.3–3 GHz. Measurements were made on excised tissues, in vitro in the laboratory, to carry out dielectric tests on sample tissues. Each dataset for a brain tissue was parametrized using the Cole–Cole expression, and the relevant Cole–Cole parameters for four tissue types are provided. A comparison was made with the database available in literature for other animals and human brain tissue. Results of two types of tissues (white matter and skull) showed systematic variation in dielectric properties as a function of animal age, whereas no significant change related to age was noticed for other tissues. Results provide critical information regarding dielectric properties of animal tissues for a realistic animal head model that can be used to verify the validity and reliability of a microwave head scanner for animals prior to testing on live animals. Bioelectromagnetics. 37:549–556, 2016. © 2016 Wiley Periodicals, Inc.